A Theoretical Approach to the Application of Command Responsibility for Domain over Organized Power Structures to High Corruption Cases - Guimaray, Erick (2019)
Organized crime can start within the State itself, even from its hierarchical and normative channels, in order to assure the effectiveness of their crimes. High corruption as a criminological category describes the synergy between political and economic power; thus, it obligates us to analyze the importance of the structural organization factor. Taking into account the current cases of political corruption that involve all Peruvian Presidents from the year 2000 onwards, we argue that the use of imputation criteria vastly used in doctrine, but no so much by our justice operators, could be a viable option that helps in the judgment of high officials at the apex of the Administration. Specifically, the application of the thesis of command responsibility for domain over organized power structures to high corruption cases.